The Utilization of the Topsis Me The Utilization of the Topsis Method in Supporting the Decision to Choose the Best High School or Vocational School - windapertiwi hamia; Iik Eliyana Purnama Sari (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2020)
School is one of the places to study. There are so many schools that can be alternatives for learning places, making students successfully graduate from Junior High School or Madrasah Tsanawiyah tends to be confused about which school is the best for them to take to a higher level. In 2019, there were around 7,168 students from 125 Juniors High Schools or Madrasah Tsanawiyah and there were around 52 Senior High or Vocational Schools in East Kotawaringin. The method that can be used to help make decisions is to use the TOPSIS or Technique for Order Preference by similarity to the Ideal Solution method. The topsis method is a method that can provide a way out of a number of alternatives where there will be a solution, which is the best alternative and the worst alternative to the alternative problems. Here the authors provide a number of data with 8 alternative high schools or public vocational schools and 8 criteria used to support this method. Based on this research, the results obtained are SMA Negeri 1 Sampit is worth 22.3%, SMA Negeri 2 Sampit is worth 91.87%, SMA Negeri 3 Sampit is worth 98.52%, SMA Negeri 4 Sampit is worth 91.22%, SMK Negeri 1 Sampit is worth 97.68%, SMK Negeri 2 Sampit is worth 97.47%, SMK Negeri 3 Sampit is worth 0.43%, and SMK Negeri 4 Sampit is worth 84.51%. With this method, students can choose which high school or public vocational school has the best alternative value.